Updates on Pharmacologic Management of Microvascular Angina - Mosayeb Soleymani; Farzad Masoudkabir; Mahsima Shabani; Ali Vasheghani-Farahani; Amir Hossein Behnoush; Amirmohammad Khalaji (Hindawi-Wiley, 2022)
Microvascular angina (MVA), historically called cardiac syndrome X, refers to angina with nonobstructive coronary artery disease. This female-predominant cardiovascular disorder adds considerable health-related costs due to repeated diagnostic angiography and frequent hospital admissions. Despite the high prevalence of this diagnosis in patients undergoing coronary angiography, it is still a therapeutic challenge for cardiologists. Unlike obstructive coronary artery disease, with multiple evidence-based therapies and management guidelines, little is known regarding the management of MVA. During the last decade, many therapeutic interventions have been suggested for the treatment of MVA. However, there is a lack of summarization tab and update of current knowledge about pharmacologic management of MVA, mostly due to unclear pathophysiology. In this article, we have reviewed the underlying mechanisms of MVA and the outcomes of various medications in patients with this disease. Contrary to vasospastic angina in which normal angiogram is observed as well, nitrates are not effective in the treatment of MVA. Beta-blockers and calcium channel blockers have the strongest evidence of improving the symptoms. Moreover, the use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, statins, estrogen, and novel antianginal drugs has had promising outcomes. Investigations are still ongoing for vitamin D, omega-3, incretins, and n-acetyl cysteine, which have resulted in beneficial initial outcomes. We believe that the employment of the available results and results of the future large-scale trials into cardiac care guidelines would help reduce the global cost of cardiac care tremendously.